Cardioprotective effect of silymarin nanoemulsion on 5‐fluorouracil‐induced cardiotoxicity in rats. Issue 7 (11th April 2022) - Safarpour, Soheila; Safarpour, Samaneh; Moghadamnia, Ali A.; Kazemi, Sohrab; Ebrahimpour, Anahita; Shirafkan, Fatemeh; Mansoori, Razieh; Golchoobian, Ravieh
Abstract: 5‐Fluorouracil (5‐FU)‐associated cardiotoxicity has been ranked as the second most common cause of cardiotoxicity induced by chemotherapeutic drugs after anthracyclines. In the present study, we investigated the protective impacts of silymarin (SIL) and silymarin nanoemulsion (SLN) against cardiotoxicity caused by 5‐FU in rats. Thirty male Wistar rats were divided into six groups as follows: control, SLN (5 mg/kg), SIL (5 mg/kg), 5‐FU + SLN, 5‐FU + SIL, and 5‐FU. Cardiotoxicity was induced by a single intraperitoneal injection of 5‐FU (100 mg/kg). The control group received an intraperitoneal injection (ip) of normal saline and the treatment groups received ips of SIL and SLN for 14 days. 5‐FU resulted in significant cardiotoxicity, represented by an increase in the serum levels of cardiac enzymes and malondialdehyde, as well as cyclooxygenase‐2 (COX‐2) and tumor necrosis factor‐α (TNF‐α) expression, and histopathological degeneration. 5‐FU treatment also induced a decrease in body weight, total antioxidant capacity (TAC), and catalase values. Evaluation of electrocardiographic parameters in 5‐FU‐treated rats showed increases in the ST segment, QRS duration, and RR interval. Treatment with SIL and SLN reduced oxidative stress, cardiac enzymes, histopathological degeneration, and the expression of TNF‐α and COX‐2 in cardiac tissue. Our results demonstrated that treatment with SIL and SLN significantly improved cardiotoxicity induced by 5‐FU in rats. Abstract : The protective effects of silymarin (SIL) and silymarin nanoemulsion (SLN) against cardiotoxicity caused by 5‐fluorouracil (5‐FU) were investigated in rats. Treatment with SIL and SLN reduced oxidative stress, cardiac enzymes, histopathological degeneration, and the expression of tumor necrosis factor‐α and cyclooxygenase‐2 in cardiac tissue, thus significantly ameliorating the cardiotoxicity induced by 5‐FU in rats.